1997
DOI: 10.1590/s0100-879x1997000500009
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and acetylcholinesterase activity of the myenteric plexus of the wild mouse Calomys callosus

Abstract: The myenteric plexus of the digestive tract of the wild mouse Calomys callosus was examined using a histochemical method that selectively stains nerve cells, and the acetylcholinesterase (AChE) histochemical technique in whole-mount preparations. Neuronal density was 1,500 ± 116 neurons/cm 2 (mean ± SEM) in the esophagus, 8,900 ± 1,518 in the stomach, 9,000 ± 711 in the jejunum and 13,100 ± 2,089 in the colon. The difference in neuronal density between the esophagus and other regions was statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…The myenteric plexus as an incompact and irregular plexo-ganglionic network with different expression of AChE activity was observed in the wild mouse (Calomys callosus), hamster, rat and guinea pig. In these species the wall of the oesophagus contained striated muscles [16][17][18][19]. A similar level of development of the Auerbach plexus was found in chinchilla.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The myenteric plexus as an incompact and irregular plexo-ganglionic network with different expression of AChE activity was observed in the wild mouse (Calomys callosus), hamster, rat and guinea pig. In these species the wall of the oesophagus contained striated muscles [16][17][18][19]. A similar level of development of the Auerbach plexus was found in chinchilla.…”
Section: Discussionsupporting
confidence: 63%
“…An AChE-positive network containing first-order (thicker) and second-order fibres with neurons in nodes was observed in wild mouse (Calomys callosus) [16]. Varicosities-forming fluorescent fibres represented the adrenergic structures of this plexus visible both in ganglia and in the connecting bundles.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…7,9,11,12 In the present investigation, this technique has shown that the NADH reaction can be used to stain neurons in the tissues taken from chagasic animals. Using this technique, it was observed that in this experimental group there were areas in which the ganglion neurons were absent, in some areas no plexus was seen, but in others an anatomically normal plexus was seen.…”
Section: Discussionmentioning
confidence: 65%
“…In a previous study, we examined the morphology of the myenteric plexus of the digestive tract of Calomys callosus (10) in view of the fact that the different effects of chagasic infection on the enteric plexuses of different species may be due to the structure of the plexuses.…”
Section: Introductionmentioning
confidence: 99%